Il giovane favoloso - Apparat 1978- (01 Distribution, 2015)
"Based upon the short but fruitful life of illness-racked Italian poet and philosopher Giacomo Leopardi." [imdb.com]
Original: Italien 2014
Bildformat 1.85:1 (anamorph)
contenuti extra: altre scene ; backstage ; trailer
Keywords: Leopardi, Giacomo -- 1798-1837; Film; DVD-Video